Characterization of SUPPRESSOR OF MAX2 1-LIKE (SMXL) Genes in ‘duli’ (Pyrus betulifolia L.) and Expression Analysis of PbSMXLs in Response to Plant Growth Regulators and Salt Stress - Shuai Yuan; Weilong Zhang; Yuxing Zhang (Agronomy)
SUPPRESSOR OF MAX2 1-LIKE (SMXL) proteins are negative regulators of strigolactone (SL) signal transduction that play an important role in regulating plant branching and responses to abiotic stress. Here, we studied the role of SMXL proteins in pear growth, development, and stress resistance. A total of 18 SMXL members were characterized in ‘duli’. All SMXL members were localized to chloroplasts. Chromosome mapping analysis showed that the members of this family were unevenly distributed on 14 chromosomes. Gene fragment replication analysis showed that there were no tandem repeat genes in PbSMXLs, and 12 pairs of homologous genes were fragment duplications. There were 30 pairs of homologous genes between ‘duli’ and apples, and 17 between ‘duli’ and Arabidopsis thaliana. Analysis of cis-acting elements showed that there was a large number of photo-effector elements, short-effector elements, hormone-responsive elements, and abiotic stress-responsive elements in the promoter sequences of this family. Analysis of enzyme activity and endogenous SL showed that β-carotenoid isomerase (D27), carotenoid cleavage dioxygenase 7 (CCD7), lateral branch oxidoreductase (LBO) levels, and SL content were higher in ‘duli’ roots and leaves compared in the control under exogenous GA3 (gibberellin 3), IAA (indole-3-acetic acid), GR24 (synthetic SL analog), and NaCl. Most SMXL genes in ‘duli’ were highly expressed in branches and axillary lobes, but their expression was low in fruits. qRT-PCR analysis revealed that eight PbSMXL genes were responsive to GA3, PAC (Paclobutrazol), IAA, ABA (abscisic acid), GR24, and Tis108 (SL biosynthesis inhibitor). PbSMXLs responded positively to salt stress. The expression of PbSMXL6 and PbSMXL15 was significantly induced under salt stress. The expression of PbSMXL7, PbSMXL10, and PbSMXL15 was significantly induced by Tis108 treatment. The results of this study enhance our understanding of the role of SMXL genes in the responses to plant growth regulators and salt stress. Our findings will also aid future studies of the functions of SMXL genes in ‘duli’.